Reported Side Effects of COVID-19 Vaccination among Adults in Saudi Arabia: A Cross-Sectional Study - Fahad Alhowaymel PhD, RN; Mohammed A. Abdelmalik PhD, RN; Almoez M. Mohammed MSN, RN; Mohamaed O. Mohamaed PhD, RN; Atallah Alenezi PhD, RN (SAGE Publishing, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2, is a major international crisis. Although vaccination is the only hope to end this pandemic, adverse effects attributable to vaccines are still being reported. Active surveillance is critical for generating near-real-time, high-quality evidence for potential safety hazards, allowing us to respond quickly to vaccination Purpose To investigate the prevalence of side effects following COVID-19 vaccination with Oxford-AstraZeneca among adults in northwestern Riyadh Province, Saudi Arabia. Methods This is a cross-sectional and community-based study performed among individuals who had received any type of COVID-19 vaccination. A convenience sampling method was used to collect data using an online survey. Results A total of 222 individuals responded to the survey, and the majority frequently reported both localized and systemic side effects after vaccination. The most reported side effects include pain at the site of injection, myalgia, headache, and fever. Some demographic factors were significantly associated with the reported post-vaccination side effects. Conclusion The most prevalent side effects experienced by individuals after receiving the COVID-19 vaccine were determined in this study. Prior to the administration of a vaccination, counseling programs should be established to help people understand and deal with the possible side effects, with a special focus on demographic differences.